Diabetes is causally associated with increased breast cancer mortality by inducing FIBCD1 to activate MCM5-mediated cell cycle arrest via modulating H3K27ac - Binbin Tan; Yang Liu; Qianqian Chen; Weijie Yang; Wenhan Yang; Kaiping Gao; Li Fu; Tiantian Zhang; Penglong Chen; Yongyi Huang; Yuting Wang; Guoqiang Zhang; et al. (Cell Death and Disease)
Abstract Breast cancer (BC) is the most common tumor worldwide and it has been recognized that up to one third of BC patients have co-existing diabetes mellitus (DM) (BC-DM). Although many observational studies have indicated an association between DM and BC, the causal relationship of DM and BC prognosis remained uncertain and the molecular mechanisms underlying BC-DM are largely unclear. In this study, we used causal inference methods, including g-computation (GC), inverse probability of treatment weighting (IPTW), targeted maximum likelihood estimation (TMLE), and TMLE-super learner (TMLE-SL), to comprehensively analyze the association of DM with BC mortality in a cohort of 3386 BC patients. We found that the adjusted odds ratios (OR) and 95% confidence intervals (95% CI) for 5-year mortality in BC-DM patients were 1.926 (1.082, 2.943), 2.268 (1.063, 3.974), 1.917 (1.091, 2.953), and 2.113 (1.365, 3.270), respectively. Further transcriptomic and qPCR analyses identified that FIBCD1 was highly expressed in BC-DM tumor tissues and in BC cells under hyperglycemia conditions. Functionally, upregulation of FIBCD1 promoted proliferation, migration, and invasion capacities of BC cells in a glucose level-dependent manner. While knockdown of FIBCD1 suppressed BC tumor growth in diabetic mice. Integrated RNA-seq and Ribo-seq analysis revealed that MCM5 was a target of FIBCD1. Mechanistically, hyperglycemia-activated FIBCD1 promoted MCM5 expression to induce S-phase cell cycle arrest by upregulating histone H3K27ac levels in MCM5 promoter via the PDH-acetyl-CoA axis. Our findings provide new evidence that co-existing DM has a causal effect on overall mortality in BC-DM patients. Targeting FIBCD1 may be a promising therapy for BC-DM.